2023
DOI: 10.3390/su15086645
|View full text |Cite
|
Sign up to set email alerts
|

Passengers’ Perception of Satisfaction and Its Relationship with Travel Experience Attributes: Results from an Australian Survey

Abstract: Rail, one of the most sustainable modes of transport, is vital in carrying mass passengers in many urban cities. Passengers’ satisfaction with railway services is mostly discussed in the context of service quality in the literature. However, limited studies have considered other attributes that may influence passengers’ satisfaction, such as their travel experience and issues encountered. This study aims to systematically model passengers’ satisfaction and its relationship with travel experience attributes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…Following up on the research of de Avila Gomide et al ( 2005) [1], the authors considered that a certain pattern has been revealed, according to which the more often passengers use public transport, the more positively they perceive transport accessibility and its individual elements. This is in line with the marketing concept [2,13] and allows the results of this study to be used to evaluate customer satisfaction factors and their impact on customer loyalty and further frequency of public transport use, which is combined with the research described previously [14,15].…”
Section: -1-findings Of the Studysupporting
confidence: 55%
See 1 more Smart Citation
“…Following up on the research of de Avila Gomide et al ( 2005) [1], the authors considered that a certain pattern has been revealed, according to which the more often passengers use public transport, the more positively they perceive transport accessibility and its individual elements. This is in line with the marketing concept [2,13] and allows the results of this study to be used to evaluate customer satisfaction factors and their impact on customer loyalty and further frequency of public transport use, which is combined with the research described previously [14,15].…”
Section: -1-findings Of the Studysupporting
confidence: 55%
“…It is a holistic affective construct after the service experience that forms the customer experience [13,14]. The importance of this kind of research for evaluating factors of customer satisfaction and its implication on customer loyalty and further frequency of public transport use is underlined in the literature [15]. The relationships between public transport usage and perceived service quality are studied in large urban agglomerations [16], and it is stated that "passengers' perception of satisfaction based on travel experience attributes [17].…”
Section: -Literature Reviewmentioning
confidence: 99%
“…The study deduced that increasing the number of bus stops and lines around metro stations was the most effective method for enhancing passenger transfer numbers, with augmenting the bus lines near stations proving more influential than merely adding more stops. Additionally, Yang et al [21] developed a theoretical model to assess passengers' overall satisfaction. Using four attribute categories-traveler, trip, service, and others-they validated their model with feedback from 429 metro train passengers in Melbourne, Australia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fan et al [20] highlighted the social benefits of Denver's LRT, including its potential to enhance accessibility and social inclusion. Furthermore, Yang et al [21] developed a model evaluating metro train passengers' satisfaction in Melbourne. They considered various factors such as trip details, service quality, and individual traveler attributes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined passengers' behaviors or perceptions, each with a different focus [10][11][12][13]. Most of these studies have investigated user-induced delays.…”
Section: Introductionmentioning
confidence: 99%